Immunomodulatory Effects of Mesenchymal Stromal Cells Revisited in the Context of Inflammatory Cardiomyopathy - Kapka Miteva; Sophie Van Linthout; Hans-Dieter Volk; Carsten Tschöpe (Hindawi Limited, 2013)
Myocarditis is a common inflammatory cardiomyopathy, associated with cardiomyocyte apoptosis, which can lead to chronic left ventricular dysfunction. Under conventional heart failure therapy, inflammatory cardiomyopathy typically has a progressive course, indicating a need for alternative therapeutic strategies to improve long-term outcomes. Experimental and clinical studies consistently support the application of cellular transplantation as a strategy to improve myocardial function. Mesenchymal stromal cells (MSCs) mediate distinct paracrine effects supporting endogenous regeneration, but most important are their remarkable immunoregulatory properties. In this review, an overview of current knowledge on immunopathology in myocarditis will be given. Furthermore, current research regarding the immunomodulatory properties of MSCs in the context of myocarditis will be discussed. Finally, the impact of MSC priming by the environment on their functionality and the advantages of systemic administration of MSCs under myocarditis are outlined.